Dosimetric Comparison of Helical Tomotherapy, Volume-Modulated Arc Therapy, and Fixed-Field Intensity-Modulated Radiation Therapy in Locally Advanced Nasopharyngeal Carcinoma - Lu, Shan; Fan, Huiqi; Hu, Xueyuan; Li, Xin; Kuang, Yingying; Yu, Deyang; Yang, Shanshan (Frontiers in Oncology, 2021)
Objective: To compare the dosimetric parameters of different radiotherapy plans (helical tomotherapy [HT], volume-modulated arc therapy [VMAT], and fixed-field intensity-modulated radiation therapy [FF-IMRT]) for locally advanced nasopharyngeal carcinoma (NPC). Methods: A total of 15 patients with locally advanced NPC were chosen for this retrospective analysis and replanned for HT, VMAT, and FF-IMRT. The prescribed planning target volume (PTV) dose for the primary tumor and metastatic lymph nodes was 70 Gy (2.12 Gy/fraction, delivered over 33 fractions). The prescribed PTV dose for the high-risk subclinical region was 59.4 Gy (1.8 Gy/fraction, delivered over 33 fractions). The dosimetric parameters of the PTV and organs at risk (OARs) and the efficiency of radiation delivery were assessed and compared using the paired-samples t-test. Results: Compared with VMAT and FF-IMRT plans, HT plans significantly improved the mean conformity index (CI) and homogeneity index (HI). The HT plans reduced the maximum doses delivered to OARs, such as the brainstem, spinal cord, and optic nerves, and significantly reduced the volume delivered to the high-dose region, especially when examining the V30 value of the parotid glands. However, VMAT reduced the treatment time and improved the efficiency of radiation delivery compared with HT. Conclusions: For locally advanced NPC, the results showed that HT and VMAT possessed better target homogeneity and conformity, reducing the dose delivered to OARs compared with conventional FF-IMRT, with HT achieving the best effect. Among the techniques studied, VMAT had the shortest radiation delivery time. The results of this study can provide guidance for the selection of appropriate radiation technologies used to treat patients with locally advanced NPC who are undergoing concurrent chemoradiotherapy.